PREDICTION OF GROUND VIBRATIONS DUE TO CONSTRUCTION BLASTS IN DIFFERENT TYPES OF ROCK - Tripathy G.R.; Gupta I.D. (My University, 2002)
A knowledge of the level of peak ground motion expected at a site from detonation of a known charge weight per delay at a specified distance is necessary for planning a safe blasting operation. The seismic wave energy associated with the blast induced ground vibration decreases with distances due to decay of both the amplitude and the frequency of vibration. The attenuation of ground motion depends mainly on the charge weight, frequency content of wave motion, and the elastic properties of the transmitting medium. The interrelationship between the charge weight, distance and the amplitude of the ground motion forms the basis of describing an attenuation law.